Symptoms, attitudes and treatment perceptions of vulvo-vaginal atrophy in UK postmenopausal women: Results from the REVIVE-EU study. Issue 2 (June 2020) - Domoney, Claudine; Short, Hannah; Particco, Martire; Panay, Nick
Objectives: To describe the attitudes and perceptions of postmenopausal women from the United Kingdom regarding menopause, vulvo-vaginal atrophy and its therapeutic management. Study design: Post hoc analysis of the United Kingdom population from the REVIVE-EU Study. Main outcome measures: The survey contained questions about women's knowledge of menopause and vulvo-vaginal atrophy symptoms, impact on their life and sexual activities, communication with healthcare professionals and treatments. Results: The most frequent symptom of menopause was hot flushes (75%). Vulvo-vaginal atrophy symptoms had a significant impact on participants' ability to enjoy sexual intercourse (66%), spontaneity (62%) and ability to be intimate (61%); however, only 68% of women had been to their healthcare professional for advice. Half of the sample expected that doctors would initiate a discussion of menopausal symptoms and sexual health, but was in fact rare (5%). Only 27% were under current treatment without a clear therapy pattern, of which 43% used vaginal over-the-counter treatments, 28% prescription (Rx), and 13% both. Efficacy was the main limitation for over-the-counter treatments, while for Rx products were side effects and safety. Women highlighted the restoring of the natural condition of the vagina as the main goal for a treatment (35%). Many United Kingdom women did not feel the need to see any healthcare professional for their gynaecological symptoms. Overall satisfaction with treatment was only 44%. Conclusions: Vulvo-vaginal atrophy remains underdiagnosed and undertreated in United Kingdom. There is a lack of coherent discussion about vulvo-vaginal atrophy symptoms with clinicians. Many United Kingdom healthcare professionals could improve proactive communication with patients about vulvo-vaginal atrophy.